Prediction of Myostatin on Carcass Composition in Crossbred Lambs - Justice, Susan M (J Anim Sci, 2021)
In order to maintain consumer acceptance of lamb meat, producers are aiming to produce leaner lambs through breeding for certain carcass characteristics. The Texel breed is known for its superior muscling phenotype due to a myostatin mutation. Because of this mutation, Texel and Texel cross lambs have been shown to have improved carcass lean with less fat in various locations throughout the carcass. The objective of this study was to observe the impacts of different sire and dam breeds on carcass composition. Lambs (n = 41) were produced by mating two dam breeds (Southdown or Suffolk) and two sire breeds (Southdown or Texel). Lambs were harvested and a hot carcass weight was obtained. At 24 h postmortem, a chilled carcass weight was taken, and each carcass was split in half. The left side of the carcass was cut into the four primal cuts and scanned using a DXA. The right half was used for standard carcass variables. After DXA scans, each primal was weighed and the major muscles were dissected from the primal cuts and weighed. Subsamples of muscles were used for total lipid analysis and Warner-Bratzler Shear Force testing. DXA scans showed a difference in the primal cut mass (P = 0.0207) with the Suffolk-Texel cross having the highest average primal cut mass at 12.52 kg. Southdown-Southdown lambs had the highest fat percentage (dam P = 0.0398; sire P = 0.0116). Dam breed had a more significant effect on muscle toughness (P < 0.0035). Southdown sired lambs had a higher SFA (P = 0.0046) and MUFA (P < .0001) but Texel sired lambs had a higher overall fatty acid ratio (P < .0001). On average, the Suffolk-Texel cross was shown to have heavier average weight for the primal cuts in the rack and leg, which are where some of the more profitable cuts of meat are located.